Cissus quadrangularis Linn. Extract Reduces High Glucose Induced Inhibition of In Vitro Proliferation and Matrix Mineralization in MG-63 Cells - Gupta, Madhu; Arshad, Md (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The aim of this study was to evaluate the effect and mechanism of action of ethanolic extract of Cissus quadrangularis Linn. stem in an in vitro system using MG-63 (osteoblast-like) cells. Cells were pre-exposed to high glucose (45 mmol/l). Insulin was used as positive control. To determine whether C. quadrangularis (CQ) extract could prevent hyperglycaemia induced oxidative stress, and apoptosis we performed reactive oxygen species generation using 2’,7’-dichlorofluorescin diacetate and propidium iodide staining for apoptosis. For cell proliferation, we carried out cell viability (MTT) assay. Further, alkaline phosphate assay and alizarin staining were done to study the matrix mineralization. High glucose (45 mmol/l) significantly (P < 0.001) inhibited the cell viability and matrix mineralization, and induced apoptosis as compared to physiological control. C. quadrangularis extract as well as insulin treatment significantly (p < 0.001 versus high glucose) restored the cell viability, cell differentiation and bone nodule formation. Thus, ethanolic extract of C. quadrangularis stem prevents the antiproliferative effect of high glucose. Dhaka Univ. J. Pharm. Sci. 16(2): 159-164, 2017 (December)